Health-related lifestyles: how they have changed after the COVID-19 pandemic occurring in Italy. (20th October 2021) - Minardi, V; Contoli, B; Possenti, V; Lana, S; Luzi, P; Masocco, M
Abstract: Background: The COVID-19 pandemic has fully affected the global community and will generate long-term consequences on social and individual life overall. Methods: Since their start, the two Italian population-based surveillance systems PASSI (18-69yy) and PASSI d'Argento (65+) have investigated health-related lifestyles. The continuous monthly data collection allows observation of changes in the short, medium and long terms. We compared prevalence of tobacco and alcohol use, physical activity, PA, or inactivity, PI, before and after March 2020, to evaluate temporal trends with particular concern to changes due to the pandemic. Results: Sedentariness has been growing among inactive adults but in pandemic time, we observed a 10% significant reduction compared to 2019, due to a significant increase of spare time PA from 42% (2019) to 45% (2020) and a reduction of spare time PI from 42% to 39%. Despite a stable trend, elderly increased significantly PI, from 40% (2019) to 43% (2020). PI goes from 46% to 52% among Southern residents and from 45% to 53% in poorly educated people. Since 2008, at-risk alcohol consumption gradually increased in adults because of binge-drinking and between meals modalities. In 2018, a tendency inversion started and finds confirmation during the pandemic: binge-drinking decreases significantly from dal 9.5% (2019) to 8.2% (2020), between meals from 9.4% to 8.6%. During the pandemic, elderly increase alcohol consumption significantly, from 39% (2019) to 45% (2020), attributable to changes in moderate use by women: 17% in 2019 vs. 25% in 2020 overall; from 20% to 30% in highly educated and from 15% to 21% in poorly educated. It seems the pandemic did not change smoking percentages. Conclusions: Monitoring the impact of the COVID-19 pandemic is crucial to understand strategies for tackling behavioural risk factors for noncommunicable diseases that, even in pandemic, represent the main burden to disability and deaths in Italy. Key messages: Monitoring the impact of the COVID-19 pandemic is crucial to understand strategies for tackling behavioural risk factors for noncommunicable diseases. Having an ongoing Behavioral Risk Factor Surveillance System is an opportunity to misure and evaluate the impact of a shock as Covid-19 pandemic.